Zapisz w jak najprostszej postaci
a) 4y x (3y) / -6
B) 6k x 2y x 5k / 1/6 =
c) 8x - (4x + 6y --5) - ( - 5y + 8x -2) =
zredukuj wyrazy podobne
a) a4 + 2b - 5a - 7b + 8a +3b =
b) 13x^2 - 22y^2 - 6x^2 + 2y^2 =
zapisz wyrażenia
iloczyn liczby -z i sumy k + m



Odpowiedź :

Odpowiedź:

a)

4y x (3y) / -6 = 12y²/(-6) = -2y²

B)

6k x 2y x 5k / 1/6 = 60k²y * 6 = 360k²y

c)

8x - (4x + 6y - 5) - ( - 5y + 8x -2) = 8x - 4x - 6y + 5 + 5y - 8x + 2 = -4x - y + 7

zredukuj wyrazy podobne

a)

a^4 + 2b - 5a - 7b + 8a + 3b = a^4 + 3a - 2b

b)

13x^2 - 22y^2 - 6x^2 + 2y^2 = 7x² - 20y²

zapisz wyrażenia

iloczyn liczby -z i sumy k + m

-z(k + m)

Szczegółowe wyjaśnienie: